The Allure of Race: From New Lefts to New Times - Torres, Rodolfo D.; Kyriakides, Christopher (My University, 2012)
This article examines conceptual obstacles to emancipation which have emerged historically within Left theory on both sides of the Atlantic, concerned primarily with "class versus race" debates spanning from the post-war Hegelian moment to the post-structural present. While the "cultural turn" promised to give voice against structuralist silencing, the critical subject of emancipation has been defaced, eradicated such that we currently have no theoretical place from where to build an emancipatory project. We must clear an analytical space through which a renewed subject of liberation can be founded. In drawing out theoretical continuity and change across varied temporal and spatial locations- Fanon/Sartre and the French-Algerian encounter; Gilroy/Miles and British urban unrest-the article explores how the Left imaginary has lost its theoretical integrity, especially in its Foucauldian gaze, and is currently unable to provide a robust vision, beyond self-other interplay, of emancipatory change.
Keywords: Race; Culture